Towards Fairness in Cash on Delivery Systems: Comparative Insights from Indonesian Consumer Law and Sharia Economic Justice (Contrarius Series: Law & Social Justice, 2026)
The Cash On Delivery (COD) system is one of the payment methods frequently used, in which consumers pay for the ordered products upon receiving them. Although it provides convenience, this system often causes problems, especially related to transaction cancellations by consumers after delivery has been made by the business operator. Such cancellations can result in significant losses for the business operator, both in terms of operational costs, shipping, and business reputation. Therefore, it is important to analyze how legal protection for business operators is regulated in the context of Law No. 8 of 1999 on Consumer Protection and also to consider the perspective of Islamic economic law principles, which can provide guidance for fairer business practices. The type of research used is library research with a normative juridical approach, which refers to research based on legal norms contained in legislation and the principles of Islamic economic law. In Law No. 8 of 1999, legal protection is regulated for business actors against losses caused by the unilateral cancellation of transactions by consumers, although the consumer's right to cancel transactions is still recognized. On the other hand, in Islamic economic law, the principles of justice, good faith, and prohibition of uncertainty require transparency and clear policies regarding transaction cancellations.